Edukasi Kader dalam Upaya Pencegahan dan Penanggulangan Stunting di Kecamatan Mondokan Kabupaten Sragen - Anik Lestari; Diffah Hanim (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Nowadays stunting has become the most observed on nutrition issues by the Indonesian government because stunting does not only cause physical abnormalities but also cognitive impairment in todlers so that as adults they will have low productivity. The aim of this community service was to increase the knowledge of certain community groups (health nutrition cadres) in preventing stunting in todlers. With the process of diffusion of knowledge, it is expected that there will be improvement in behavior of the target audience in carrying out their duties as posyandu cadres. This community service agenda are implemented through two activities. By having lectures and QnA sessions. The second method namely “cerdas cermat” was used to assess whether the counseling material can be understood by the participants. A team answer correctly they will be given a